The effects of value innovation on companies' performance in Yemen telecommunications industry - Mohammed Ahmed, Mohammed Hajar (2021)
Innovation has been recognized to be the key to growth and survival for the telecommunications industry. Globalization, liberalization, and privatization, which are the most associated terms with this sector, resulted in fierce competition and make it more challenging for telecommunications firms to expand their market share, and hence, increase customer base, sales volume, and ultimately profit. The new strategy to succeed is innovation differentiation which leads to break out of the competition and create an uncontested market. That can be done by the provision of high-value innovative services which translate into consumer satisfaction and promote customer loyalty. This study aims to propose a new theoretical model to enhance the value innovation practices. It studies the contribution of value innovation in the telecommunications industry in Yemen and its effects on customer satisfaction, customer loyalty, firm performance sustainable growth. Accordingly, the study adopts a combination of quantitative and qualitative research design. Firstly, a questionnaire survey was conducted and data collected for 304 respondents of mobile service providers in Yemen to examine the effects of value innovation on customer satisfaction, customer loyalty, firm’s performance, and firm’s sustainable growth. Besides that, the generated data and proposed model were measured and analyzed by using the Statistical Package for Social Science (SPSS) and SmartPLS software. In consequence, the results empirically validated the theoretical research model confirming the significance of value innovation approach to achieve through promoting customer satisfaction and loyalty. Secondly, 10 semi-structured interviews for telecommunications senior executives and experts were conducted to deep dive into Yemen telecommunications issues and underlying problems and difficulties regarding innovation in the Yemen telecommunications industry. The generated data were analyzed using descriptive analysis, coding, and content analysis to report the outcomes of conducted interviews and provide a concrete foundation of information and facts of the nature of innovation management in the Yemen telecommunications industry. Thus, 19 sub-themes were synthesized and discussed with relevant to four main categorized themes including innovation management practices and organizational difficulties and challenges; World Trade Organization (WTO) accession and market liberalization; value innovation adoption; and future aspirations and expectations with regards to innovation. Finally, the integrated results and outcomes were employed to propose a roadmap that could efficiently enhance value innovation activities, promote customer satisfaction and loyalty, growth.